Higher frequency of medication overuse headache in patients attended by neurologists in Lima, Peru - Novoa, María Elena; Bordini, Carlos Alberto (Headache Medicine, 2021)
Background The type of medical care received (self-medication and/or medical care provided by a general practitioner or a neurologist) may be associated with differences in the frequency of medication overuse headaches. Method This cross-sectional analytical study included 222 records of patients with chronic daily headaches seen at the National Institute of Neurological Sciences Outpatient Unit in Lima, Peru. A pre-designed questionnaire was used to assess and categorize patients with frequent and chronic headaches. Results Ninety-four patients (42.34% of those with chronic daily headaches) met the criteria for medication overuse headache. Of these, 19 (28%) self-medicated, 22 (36%) consulted with the general practitioner, and the highest proportion of subjects, 53 (58%), consulted with a neurologist. On bivariate analysis, subjects who had received care from a general practitioner and self-medicated were 38% and 51% less likely to have MOH than the subjects who received medical care from the neurologist (p=0.012; 95% CI 0.42-0.90 and p=0.001; 95% CI 0.32-0.74). On multivariate analysis adjusting by sociodemographic and clinical factors, the association remained significant in regards to self-medication, but became marginal (p=0.055) in regard to being seen by a general practitioner. Conclusion In this study, the frequency of the headache due to overuse of medication was higher in patients attending a neurologist than those attending a general practitioner or self-medicated. This cross-sectional design cannot assess whether this reflects more severe cases looking for specialized care or more medication overuse headaches as a result of inappropriate management.